Endotoxinemia Accelerates Atherosclerosis Through Electrostatic Charge–Mediated Monocyte Adhesion. Issue 3 (19th January 2021) - Schumski, Ariane; Ortega-Gómez, Almudena; Wichapong, Kanin; Winter, Carla; Lemnitzer, Patricia; Viola, Joana R.; Pinilla-Vera, Mayra; Folco, Eduardo; Solis-Mezarino, Victor; Völker-Albert, Moritz; Maas, Sanne L.; Pan, Chang; et al.
Abstract : Background: Acute infection is a well-established risk factor of cardiovascular inflammation increasing the risk for a cardiovascular complication within the first weeks after infection. However, the nature of the processes underlying such aggravation remains unclear. Lipopolysaccharide derived from Gram-negative bacteria is a potent activator of circulating immune cells including neutrophils, which foster inflammation through discharge of neutrophil extracellular traps (NETs). Here, we use a model of endotoxinemia to link acute infection and subsequent neutrophil activation with acceleration of vascular inflammation Methods: Acute infection was mimicked by injection of a single dose of lipopolysaccharide into hypercholesterolemic mice. Atherosclerosis burden was studied by histomorphometric analysis of the aortic root. Arterial myeloid cell adhesion was quantified by intravital microscopy. Results: Lipopolysaccharide treatment rapidly enhanced atherosclerotic lesion size by expansion of the lesional myeloid cell accumulation. Lipopolysaccharide treatment led to the deposition of NETs along the arterial lumen, and inhibition of NET release annulled lesion expansion during endotoxinemia, thus suggesting that NETs regulate myeloid cell recruitment. To study the mechanism of monocyte adhesion to NETs, we used in vitro adhesion assays and biophysical approaches. In these experiments, NET-resident histone H2a attracted monocytes in a receptor-independent, surface charge–dependent fashion. Therapeutic neutralization of histone H2a by antibodies or by in silico designed cyclic peptides enables us to reduce luminal monocyte adhesion and lesion expansion during endotoxinemia. Conclusions: Our study shows that NET-associated histone H2a mediates charge-dependent monocyte adhesion to NETs and accelerates atherosclerosis during endotoxinemia. Abstract : Supplemental Digital Content is available in the text.